The Feasibility of Using the Direct Anterior Approach for Total Hip Arthroplasty or Bipolar Hemiarthroplasty to Treat Femoral Neck Fractures among the Elderly - Shigeo Ishiguro; Kunihiro Asanuma; Tomohito Hagi; Hidehiko Ohsumi; Hiroki Wakabayashi; Akihiro Sudo (Advances in Orthopedics)
Purpose. Femoral neck fractures (FNFs) are a significant cause of mortality and disability among the elderly. Total hip arthroplasty (THA) is the preferred treatment method in active, cognitively intact patients. In less active or cognitively impaired patients, bipolar hemiarthroplasty (BHA) is the practical option in Japan. Even with the direct anterior approach (DAA), clinical concerns about conducting THA in elderly patients include possible dislocations, critical complications, and medical cost-effectiveness. This study is aimed at rethinking the practical surgical indications for FNFs. Methods. Between April 2019 and March 2021, BHA patients with displaced FNF (n = 21) performed through the DAA were compared with THA patients with displaced FNF (n = 19). The perioperative complications, clinical and radiologic outcomes, and mortality were compared between groups retrospectively at six months. Results. THA patients had an increased average operation time (103.3 min vs. 89.1 min, P<0.05) and similar amounts of bleeding (183.16 ml. vs. 121.1 ml.). The percentages of patients who received biological transfusion showed no difference, with low rates of perioperative complications (4% vs. 0%) and similar mortality rates compared to BHA patients. One THA patient experienced posterior dislocation during a state of postoperative delirium. Conclusion. THA through the DAA might be a credible and safe option for FNF patients, with excellent functional outcomes and fewer surgery-related complications. Early posterior dislocation might be related to optimized offset distance and not related to leg discrepancy or other radiographic items. Hence, orthopedic surgeons should reconsider their options before conducting BPH for elderly and cognitively intact FNF patients.